2013
DOI: 10.1371/journal.pone.0081543
|View full text |Cite
|
Sign up to set email alerts
|

The JIL-1 Kinase Affects Telomere Expression in the Different Telomere Domains of Drosophila

Abstract: In Drosophila, the non-LTR retrotransposons HeT-A, TART and TAHRE build a head-to-tail array of repetitions that constitute the telomere domain by targeted transposition at the end of the chromosome whenever needed. As a consequence, Drosophila telomeres have the peculiarity to harbor the genes in charge of telomere elongation. Understanding telomere expression is important in Drosophila since telomere homeostasis depends in part on the expression of this genomic compartment. We have recently shown that the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…All transgenes were mapped at between 12-23 kb distance from TAS (43). The orange eye colour of EY08176, EY00453 and EY00802 transgenic flies corresponds to the previously reported phenotype and indicates a high level of the mini-white reporter gene expression (43,46). The EY03383 strain carries P{EPgy2} in the 2R TAS (43).…”
Section: Drosophila Ovariesmentioning
confidence: 65%
See 2 more Smart Citations
“…All transgenes were mapped at between 12-23 kb distance from TAS (43). The orange eye colour of EY08176, EY00453 and EY00802 transgenic flies corresponds to the previously reported phenotype and indicates a high level of the mini-white reporter gene expression (43,46). The EY03383 strain carries P{EPgy2} in the 2R TAS (43).…”
Section: Drosophila Ovariesmentioning
confidence: 65%
“…The Drosophila TAS regions consist of complex satellite-like repeats of 400-1800-bp in length and form heterochromatin domains that are able to induce silencing of transgenic constructs in somatic cells, a phenomenon known as telomeric position effect (58,59). The TAS regions are enriched with H3K27me3 marks and bind Polycomb group proteins (44)(45)(46). In the germline, we observed HP1, Rhi, and H3K9me3 enrichment in the EY03383 subtelomeric transgene (Fig.…”
Section: Comparison Of Subtelomeric Chromatin In Somatic and Ovarian mentioning
confidence: 89%
See 1 more Smart Citation
“…All dipteran insects have lost the telomeric repeats; it has been suggested that they use a telomerase-independent telomere maintenance system (41,42,43,44,45). In D. melanogaster, telomeres are composed of three specialized non-LTR retrotransposons, TART, HeT-A, and TAHRE and maintained mainly by retrotransposition of these elements, which have been extensively studied to date (41,42,43,46,47,48,49,50,51,52) (Fig. 3B).…”
Section: Drosophila Telomere-specific Elementsmentioning
confidence: 99%
“…We have recently described some of the chromatin proteins involved in the epigenetic regulation of Drosophila telomeres [16], [17], [18]. …”
Section: Introductionmentioning
confidence: 99%